Comparison of Experimental Rat Models in Donation After Circulatory Death (DCD): in-situ vs. ex-situ Ischemia - Arnold, Maria; Méndez-Carmona, Natalia; Wyss, Rahel K.; Joachimbauer, Anna; Casoni, Daniela; Carrel, Thierry; Longnus, Sarah (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Donation after circulatory death (DCD) could substantially improve donor heart availability. However, warm ischemia prior to procurement is of particular concern for cardiac graft quality. We describe a rat model of DCD with in-situ ischemia in order to characterize the physiologic changes during the withdrawal period before graft procurement, to determine effects of cardioplegic graft storage, and to evaluate the post-ischemic cardiac recovery in comparison with an established ex-situ ischemia model. Methods: Following general anesthesia in male, Wistar rats (404±24g, n=25), withdrawal of life-sustaining therapy was simulated by diaphragm transection. Hearts underwent no ischemia or 27 min in-situ ischemia and were explanted. Ex situ, hearts were subjected to a cardioplegic flush and 15 min cold storage or not, and 60 min reperfusion. Cardiac recovery was determined and compared to published results of an entirely ex-situ ischemia model (n=18). Results: In donors, hearts were subjected to hypoxia and hemodynamic changes, as well as increased levels of circulating catecholamines and free fatty acids prior to circulatory arrest. Post-ischemic contractile recovery was significantly lower in the in-situ ischemia model compared to the ex-situ model, and the addition of cardioplegic storage improved developed pressure-heart rate product, but not cardiac output. Conclusion: The in-situ model provides insight into conditions to which the heart is exposed before procurement. Compared to an entirely ex-situ ischemia model, hearts of the in-situ model demonstrated a lower post-ischemic functional recovery, potentially due to systemic changes prior to ischemia, which are partially abrogated by cardioplegic graft storage.